Screening for gestational diabetes mellitus: a Caribbean perspective. (17th November 2018) - Bassaw, Bharat; Fletcher, Horace; Rattray, Carole; McIntyre, Garth; Sarkharkar, Vrunda; Sankat, Sarisha; Sirjusingh, Adesh; Chinnia, Javed
Abstract: Gestational diabetes mellitus (GDM) is defined as a glucose intolerance first recognised in pregnancy. The World Health Organization (WHO) in 2015 revised the definition into either diabetes in pregnancy (DIP) which includes pre-existing diabetes (type 1 or type 2) that antedates pregnancy or diabetes diagnosed during pregnancy with the WHO diagnostic criteria for diabetes mellitus (DM) in the non-pregnant state, and GDM for milder forms of hyperglycaemia in pregnancy. The main purpose of the screening and diagnosis of GDM is to identify pregnancies in which the foetus is at a high risk of an adverse perinatal outcome, and the mother and the offspring are of serious long-term sequelae. This review of the literature provides an overview of associated prevalence, risk factors and diagnosis of GDM. It also addresses the benefits of screening with supportive evidence. Based on this review, we recommend especially in low-resourced countries such as the Caribbean, adoption of a universal screening with the two-step method.